ERP adoption by public and private organizations – a comparative analysis of successful implementations - Alves, Maria do Céu; Matos, Sergio Ivo Amaral (Journal of Business Economics and Management, 2013)
The business environment has changed dramatically in the last years. The organizations are now more complex in terms of their structure and geographical dispersion. Daily, great amounts of information are produced and, to surpass these problems, organizations have invested in Enterprise Resource Planning systems (ERP). The same trends can be detected within the public sector. The interest generated by the ERP phenomenon is growing and the particularities of the public sector make specific studies necessary. Accordingly, the aim of this paper is to examine the adoption process of ERP systems by public and private organizations. Which ERP modules are mostly adopted? Which reasons legitimate ERP adoption? Using a survey research methodology, this study reveals that the need to increase the demand for real-time information, to obtain information for decision-making and the integration of applications appear as main reasons to implement an ERP system. Although the reasons given are the same for public and private organizations, the results of this study also show that the modules implemented are slightly different; the importance or dominance of each module may differ; and the deployment time is shorter in the public sector. Since comparative studies are relatively scarce, our work helps to reduce this knowledge gap.First published online: 14 Sep 2012